Key Freedom Of Speech Development Trends In The Information Society - Антіпова, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The process of establishing information society, the accelerated pace of info exchange qualitatively transforming communicative interaction, which naturally affects the phenomenon of freedom of speech. Aim and tasks. The aim of the article is to identify key freedom of speech development trends in the information society. Research methods. The methodological tools consist of the sociocultural approach, methodological principles of systemacity and completeness. Research results. Freedom of speech is currently recognized as a sociocultural human right to freedom of expression and taking a stand on one’s worldview that do not violate the rights and freedoms of other members of society and provide the optimal info exchange process, taking into account key cultural trends of the information age. Discussion. The results of the analysis of freedom of speech phenomenon in the information era complement the conceptual development of researchers in the context of today’s global changes. Conclusion. On the one hand, Internet communications significantly widen our contemporaries’ opportunities when it comes to freedom of speech, and on the other, they can result in its levelling, information lawlessness, which can be the reason for imposing low-quality information, spreading fake messages and mind control. The responsibility of the subject of information generation not only to its consumer, but also to himself, seems to be an immediate concern. In the culture of information era, the consumer is perceived not as a passive element of communicative process, but rather as an active participant in shaping the sociocultural space. The criterion for regulating the flow of information, and therefore the freedom of expression degree, is acquiring “information taste” by the consumer.